2021
DOI: 10.26434/chemrxiv.13704094.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Wildfire-Derived Pyrogenic Carbon Modulates Organic Matter and Microbial Functioning in a Fluvial Ecosystem

Abstract: Wildfires produce large amounts of pyrogenic carbon (PyC), including particulate charcoal, known for its chemical recalcitrance and sorption affinity for organic molecules. Wildfire-derived PyC is highly mobile in the landscape and can be transported to fluvial networks where it may impact natural dissolved organic matter (DOM) and microbial biofilms. The effects of PyC on freshwater ecosystems and carbon cycling therein remain poorly investigated. To address this research gap, we used in-stream flumes with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
(28 reference statements)
0
1
0
Order By: Relevance
“…Long term release of CO 2 from PBC might be a significant loss process of C leading to isotopic enrichment of the residual PBC pool. Another study exploring the effect of pyrogenic C on stream biogeochemistry observed the release of dissolved organic matter from pyrogenic C (Bistarelli et al., 2021). The reactivity of PBC in aquatic systems provides fresh insights into its ability to actively participate in the global C cycle and the limited ability to sequester C as otherwise anticipated.…”
Section: Discussionmentioning
confidence: 99%
“…Long term release of CO 2 from PBC might be a significant loss process of C leading to isotopic enrichment of the residual PBC pool. Another study exploring the effect of pyrogenic C on stream biogeochemistry observed the release of dissolved organic matter from pyrogenic C (Bistarelli et al., 2021). The reactivity of PBC in aquatic systems provides fresh insights into its ability to actively participate in the global C cycle and the limited ability to sequester C as otherwise anticipated.…”
Section: Discussionmentioning
confidence: 99%